Randomized control trial comparing the functional outcomes of dynamic hip screw and locking plate dynamic hip screw in intertrochanteric fractures of femur - Ramachandran, Kiran; Sasidharan, Dileep; Mathew, Oommen (International Journal of Research in Orthopaedics, 2020)
Background: The objective of the study was to compare the functional outcomes of intertrochanteric fractures of the femur treated with dynamic hip screw (DHS) and locking plate DHS in elderly. Methods: 48 participants (23 in DHS and 25 in locking plate DHS) aged ≥ 50 years with intertrochanteric fracture of femur were enrolled in the present randomized open label parallel group trial conducted at Pushpagiri Institute of Medical Sciences and Research Centre during a period of 1 year. Open, pathological, other fractures in the same limb and participants with neurological involvement were excluded. Standard of care (pre and post-operative care) was given to all participants. Sociodemographic, radiological findings, fracture type and Singh’s index were recorded at baseline, 6 weeks, 3 and 6 months. Study commenced after approval from Institutional Ethics Committee and written informed consent was obtained from all study participants. Participants were randomized in 1:1 ratio using coin flip method. Quantitative variables were expressed means and medians and qualitative variables were expressed as proportions. Tests of significance were independent sample t test, Mann Whitney U test, Friedman test and Chi square test. Results: Between DHS and locking plate DHS, no significant difference in baseline parameters, neck shaft angle, tip apex distance, shortening, Harris hip score, range of motion score and length of hospital stay were observed. Conclusions: The functional outcomes and complications between DHS and locking plate DHS were not significantly different.